Konsep Pendidikan Multikultural dalam Kebijakan Publik - Juniaris Agung Wicaksono (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
This study is aimed at both of teachers and pupils to know the construction of knowledge and also need to be aware that in the received wisdom that there are diverse interpretations. Because therein strung cultural and ethnic diversity in the form of lifestyle, social experience, personal identity, opportunities for education of the individual, so the multicultural education gives multicultural competence. It is expected that learners are able to accept differences, criticism, and have a sense of empathy, tolerance for others regardless of class, status, gender, and academic skills. Multicultural be referred to as the plurality of cultures and religions. Thus maintaining the plurality will be achieved life-friendly and full of peace. Plurality of cultures is the social and political interaction between people of different way of living and thinking in a society ideal, cultural pluralism (multicultural) means the rejection of bigotry, racism, and accept the diversity of existing inclusively.